Produktivitas Kerja Aparatur Pemerintahan pada Kantor Camat Wawonii Utara Kabupaten Konawe Kepulauan - Rama, Muhamad Irfan; Sukarmin, Sukarmin; Kasmin, Kasmin (Jurnal Ilmiah Dikdaya, 2022)
Work productivity of government apparatuses at the north wawonii district office, konawe islands regency. the purpose of this study was to find out and describe the work productivity of government officials at the north wawonii district office, konawe islands regency. this research uses qualitative methods and does not use populations, because qualitative research departs from certain cases that exist in certain social situations. so the informants in the study were 1 key informant and 6 sub-district government officials. the results showed that the work productivity of government officials at the north wawonii sub-district office, konawe islands regency, could be achieved in terms of (a) capability, (b) increasing the results achieved, (c) work enthusiasm, (d) self-development, employees can be productive because they often following training or technical guidance (e) quality. the factors that influence the work productivity of government officials at the north wawonii sub-district office, konawe islands regency, consist of factors (1) motivation, with the motivation of employees being able to work more productively, (2) discipline, namely employees who work by obeying the rules and rules can be more productive in carrying out their main tasks and functions (3) work ethics, employees at work have the character, attitude and ethics of always working hard so they can be productive, (4) skills, namely employees in work are supported by work skills obtained through training and technical guidance so that they are more productive at work, (5) education, namely employees who have formal education affect the ability of employees to work. because low education with higher education is different in work productivity.